Taking Our Cities For God how to break spiritual strongholds - Dawson, John (Milton Keynes Word Publishing, 1989)
You are in the middle of an invisible spiritual war! Explore strategies for faith and prayer that can win the battle! Just imagine for a moment--living in a community where children meet to pray, crime is almost nonexistent and people fill the churches. In Taking Our Cities for God, you will explore dynamic and life-changing strategies to help you tear down the strongholds that have held your community back from its full spiritual potential. Remove the roadblocks that prevent your city from experiencing spiritual renewal and revival! This revised handbook with its thirteen-lesson study guide invites you to take part in a cleanup effort that will open the heavens above your city and allow God's blessings to flow freely. Its original printing over twelve years ago launched an era of successful prayer walks, mapping and strategic intercession. Now is the time for you to claim your spiritual authority and take your city for God!
Keywords: Dawson, John, -- 1951- Cities and towns -- Religious aspects -- Christianity. Spiritual warfare